Componentes dos sistemas purinérgico e colinérgico nos processos inflamatórios e neurológicos em roedores infectados experimentalmente com Toxoplasma gondii - Tonin, Alexandre Alberto (2014)
Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii, often leading to functional, biochemical and structural changes, especially in the central nervous system. These changes are usually accompanied by a marked immune-inflammatory response, in immunocompetent hosts. Primary infections with T. gondii stimulate production of high levels of interleukins, such as IL-12 and IFN-γ, by cells of the innate immune system, being central efforts to resistance to the disease. In terms of immune response, the purinergic and cholinergic systems have some well-defined properties, but we still without much information on the interrelation of these properties with toxoplasmosis. Thus, the objectives of this study were to evaluate the activities of the (1) E-NTPDase and E-ADA in lymphocytes; (2) AChE on total blood and lymphocytes, and BChE on serum, using the RH (virulent) strain of T. gondii, with sampling on day 5 and 10 post-infection (pi); and (3) assess the purine levels and E-ADA activity in brain, using strains RH and Me-49 (cystogenic). First assessment´s result demonstrated that the hydrolysis of ATP and ADP was increased, as well as the E-ADA activity also was increased. In the second experiment, there was an increase in AChE activity on lymphocytes and on whole blood. Finally, on the third experiment, it was found, in infection with RH, a significant increase of ATP, ADP, AMP, adenosine, hypoxanthine and xanthine levels, along with a reduction of inosine levels. Animals infected with the strain Me-49 showed increased concentrations of ATP and ADP, followed by a reduction of nucleotides and nucleosides levels. Regarding to E-ADA activity, it was observed a reduction on its activity on RH infection, and initially for Me-49 infection; however, E-ADA increased its activity, for this cystogenic at the end of the third experiment. The evaluations of E-NTPDase and E-ADA activities led to the preposition that their hydrolytic activity would be linked to a mechanism of protection against secondary tissue damage, possibly generated by an exacerbated response against T. gondii infection. Additionally, the data of AChE activity, in corresponding samples, confirm the onset of a pro-inflammatory response, corroborating with the hypothesis of necessity of a modulation mechanism. On brain tissue, the experimental model using RH strain repeated its pro-inflammatory pattern, with data of this pattern better observed in a long run, when the results of Me-49 study were evaluated. On Me-49 infection model, it was observed an increase in extracellular ATP, at the beginning of infection, with histopathology data showing inflammatory infiltrate and identification of tissue cysts later on the experiment. Finally, in this last period, it was observed a decrease in purine´s concentration, most likely as a result of the aggravation of local cellular condition, due to the disease´s evolution. Therefore, it was possible to observe that there was a direct involvement of purinergic and cholinergic systems on immunomodulation of experimental toxoplasmosis, with virulent or cystogenic strains, contributing to the establishment of an adequate immune response on the parasite, and also to a mechanism of tissue damage reduction, which is normally associated with direct parasite damage and excessive immune response.